Eleven ways to get a grip on the implementation of remote administration of high-stakes assessments - St-Onge, Christina (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
The COVID-19 pandemic rushed licensure and certification institutions, as well as many university programs, to integrate Information and Communication Technologies (ICTs) in their practices to allow for remote administrations of their exams independent of distancing measures. The Black Ice covered in this manuscript is the integration of ICTs to allow remote administration of high-stakes assessments in terms of its development, administration, and monitoring with the aim to promote the validity of score interpretation.